Exposer la sculpture au Louvre au temps de Rodin, 1860-1914 - Geneviève Bresc-Bautier (Les Cahiers de l'École du Louvre)
In the rooms of the Musée du Louvre, curators were faced with many constraints: space limited in surface, height and the repartition into rooms by the architecture of an existing palace; lateral light from windows on a single side; existing original collection; multiple improvements, influenced by the curiosity and appetite of the curators, the taste of the donors and the assignments from the Musée du Luxembourg. The Department of Sculpture was then divided into two entities: Middle Ages and Renaissance in the south wing of the Cour Carrée, modern times in the west wing. During the period under consideration, the curators sought to extend their domain by gradually taking over new spaces, in order to exhibit the medieval collections on one hand and works from the second half of the nineteenth century on the other.01 mai 2016